(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper examines how Indian women are portrayed in stories by Indian authors living outside India. It focuses on two books: “Jasmine” by Bharati Mukherjee and “The Death of a Passport” by Iqbal Ramoowalia. Both writers are part of the Indian diaspora settled in North America. In these stories, the women characters share their experiences, come to terms with their identities, and push back against challenges. The main characters, Jasmine and Seema, represent women who feel disconnected and in pain but also go through significant personal growth. Gainingideas from different writers, the paper aims to explore how women in these narratives find their voices and become more aware of themselves and their surroundings. By analyzing these stories, the paper hopes to shed light on how Indian women navigate life, find themselves and confront obstacles while living outside their homeland.